2018
DOI: 10.1186/s12891-018-2368-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolated revision meniscal repair – failure rates, clinical outcome, and patient satisfaction

Abstract: BackgroundFailure of isolated primary meniscal repair must be expected in approximately 10–25% of cases. Patients requiring revision surgery may benefit from revision meniscal repair, however, the results of this procedure remain underreported. The purpose of this study was therefore to evaluate the outcome and failure rates of isolated revision meniscal repair in patients with re-tears or failed healing after previous meniscal repair in stable knee joints.MethodsA chart review was performed to identify all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Fuch et al found high outcomes in quality of life in isolated meniscal repair, with a follow up of 3 years, measured by KOOS QOL, with a medium score of 81.8 ± 12.1. (32) In a recent retrospective study by Cinque et al (33), in 85 patients with ACL reconstruction with or without meniscal repair, they found similar outcomes in quality of life than our study, using SF-12 they found in physical components medium value of 52,8, and in mentall components they found 53,2. And also they didn't found a statiscally signi cant difference between ages and quality of life outcomes.…”
Section: Quality Of Lifesupporting
confidence: 76%
“…Fuch et al found high outcomes in quality of life in isolated meniscal repair, with a follow up of 3 years, measured by KOOS QOL, with a medium score of 81.8 ± 12.1. (32) In a recent retrospective study by Cinque et al (33), in 85 patients with ACL reconstruction with or without meniscal repair, they found similar outcomes in quality of life than our study, using SF-12 they found in physical components medium value of 52,8, and in mentall components they found 53,2. And also they didn't found a statiscally signi cant difference between ages and quality of life outcomes.…”
Section: Quality Of Lifesupporting
confidence: 76%
“…While the reoperation rates of meniscal repair is likely to be higher than that of meniscetomy at short-term follow-up. Neverthless, given the increased risk of partial meniscetomy predisposing patients to early onset degenerative changes, preversation of meniscal tissue should be attempted whenever possible [9][10][11]. However, to our knowledge, no study was conducted to assess the potential factors associated with the prevalence of meniscal repair.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with meniscetomy, meniscal repair can preserve its tissue, thus restore its biomechanical function reducing the risk of developing knee OA in the future. In the above setting, a consensus has been reached that meniscal tissue should be preserved as much as possible [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…About quality of life, Fuch et al found high outcomes in quality of life in isolated meniscal repair, with a follow up of 3 years , measured by KOOS QOL, with a medium score of 81.8 ± 12.1. [33].…”
Section: Discussionmentioning
confidence: 99%